2012
DOI: 10.1021/mp3001827
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Mechanism of Formation of Protein Microspheres in a Biphasic System

Abstract: Microspheres of bovine serum albumin (BSA) and silk fibroin are produced by applying ultrasound in a biphasic system consisting of an aqueous protein solution and an organic solvent. The protein microspheres are dispersed in an aqueous media where the protein remains at the interface covering the organic solvent. This only occurs when high shear forces are applied that induce changes to force the protein to the interface. Fourier transform infrared results indicate a large increase in the content of the β-shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 38 publications
2
70
0
Order By: Relevance
“…The results obtained are in accordance with the literature [12,21,23,53], where it is described that SF particles prepared by mechanical mixing and self-assembly process are predominantly composed by β-sheets. The formation of β-sheets increases encapsulation efficiency of small molecules and enables a tight control of the release kinetics [12,13].…”
Section: Sf-me Formationsupporting
confidence: 91%
See 2 more Smart Citations
“…The results obtained are in accordance with the literature [12,21,23,53], where it is described that SF particles prepared by mechanical mixing and self-assembly process are predominantly composed by β-sheets. The formation of β-sheets increases encapsulation efficiency of small molecules and enables a tight control of the release kinetics [12,13].…”
Section: Sf-me Formationsupporting
confidence: 91%
“…Despite that n ‐dodecane can cause cytotoxicity (according to manufacturer's product data sheet), previous work done by our research group showed that only high ratios of n ‐dodecane (above 40%) were considered toxic in the human cell line RKO (unpublished data and ). Although a proven absence of toxicity can only be evaluated with direct tests to evaluate the SF‐ME effect on cells, we may predict that the formulations produced in this study should be biocompatible and will not lead to cytotoxicity due to n ‐dodecane.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Protein nanocapsules could be prepared by various emulsification methods, such as single/double emulsions [59,60], polymerization [61], phase separation/coacervation [62], spray drying/spray congealing [63,64] and ultrasonic emulsification [65].…”
Section: Protein Nanocapsulesmentioning
confidence: 99%
“…Currently, there is a modest number of examples for the silk‐derived materials, formulated by ultrasonication. Our group reported on both bovine serum albumin (BSA) and SF‐based microspheres, formed by high‐intensity ultrasound . BSA secondary structure was not disturbed during the microsphere synthesis, but an increase in the β‐sheet content for silk was detected.…”
Section: Manipulating Silk Fibroin: Chemical and Biochemical Approachmentioning
confidence: 99%